A MXene‐Based Hierarchical Design Enabling Highly Efficient and Stable Solar‐Water Desalination with Good Salt Resistance. (20th September 2020) - Fan, Xiangqian; Yang, Yang; Shi, Xinlei; Liu, Yang; Li, Hongpeng; Liang, Jiajie; Chen, Yongsheng
Abstract: A solar‐thermal water evaporation structure that can continuously generate clean water with high efficiency and good salt rejection ability under sunlight is highly desirable for water desalination, but its realization remains challenging. Here, a hierarchical solar‐absorbing architecture is designed and fabricated, which comprises a 3D MXene microporous skeleton with vertically aligned MXene nanosheets, decorated with vertical arrays of metal–organic framework‐derived 2D carbon nanoplates embedded with cobalt nanoparticles. The rational integration of three categories of photothermal materials enables broadband light absorption, efficient light to heat conversion, low heat loss, rapid water transportation behavior, and much‐improved corrosion and oxidation resistance. Moreover, when assembling with a hydrophobic insulating layer with hydrophilic channel, the MXene‐based solar absorber can exhibit effective inhibition of salt crystallization due to the ability to advect and diffuse concentrated salt back into the water. As a result, when irradiating under one sun, the solar‐vapor conversion efficiency of the MXene‐based hierarchical design can achieve up to ≈93.4%, and can remain over 91% over 100 h to generate clean vapor for stable and continuous water desalination. This strategy opens an avenue for the development of MXene‐based solar absorbers for sustainable solar‐driven desalination. Abstract : A hierarchical MXene‐based solar‐absorbing architecture is demonstrated. The rational integration of three categories of photothermal materials enables broadband light absorption, efficient light to heat conversion, low heat loss, rapid water transportation behavior, and much improved corrosion and oxidation resistance.